Securing India: Strategic Thought and Practice - George K Tanham; TANHAM (George K); BAJPAI (Kanti P) Ed; MATTOO (Amitabh) Ed (New Delhi Manohar, 1996)
This volume contains George K. Tanham's RAND essay, 'Indian Strategic Thought', the sequel essay, 'Indian Strategy in Flux?' and commentaries by five Indian scholars. In the past, strategic thought has been dominated by the West and the former Soviet Union. In the coming years new powers, including India, will matter greatly. It is essential to study Indian strategy to understand the implications to the world as India's fortunes rise.
Keywords: Military Policy; National Security; Strategic Aspects of Individual Places; Essays